Relationship between Assertive Communication and Cyber-​​bullying in Adolescents - Kusumawaty, Ira; Yunike, Yunike; Ni Ketut, Sujati (Jurnal Kedokteran Brawijaya, 2021)
The mandatory use of online facilities during the Covid-19 period has a great opportunity to increase the problem of cyber bullying at all levels of education. The concept of assertiveness cannot be separated from cyber bullying and it is known that communicating assertively can prevent cyber bullying even though it is difficult to implement. The complexity of the psychological problems of victims of cyber bullying requires comprehensive management. This analytical descriptive study with a cross sectional approach aims to analyze the relationship between assertive communication and cyber bullying by involving 151 student participants and high school students in Palembang. The data was collected using an assertive scale and a cyber-bullying scale, which was distributed online using a Google form. From Kendall's tau-b statistical test, it is known that there is a relationship between assertive communication and cyber bullying (p=0.026). It is recommended that the education sector implement self-awareness, empathy, assertive communication and conflict resolution training to prevent the increasing number of cyber bullying's victim. The academic and managerial sectors are expected to facilitate promotion through educational media about using online facilities intelligently by respecting human dignity.